Fungi Associated With Rotten Fruits in Dhaka Metropolis - Bashar, MA; Shamsi, S; Hossain, M (Bangladesh Journal of Botany, 2012)
A total of 18 species of fungi representing nine genera were found to be associated with the rotten fruits collected from the markets of Dhaka metropolis. The fungi isolated from the fruits were Alternaria alternata ( Fr.) Keissler, Alternaria sp., Aspergillus flavus Link., A. niger Van Tiegh, A. fumigatus Fresenius, A. terreus Thorn, Colletotrichum gloeosporioides (Penz.) Sacc, Colletotrichum sp.1, Colletotrichum sp.2, Curvularia brachyspora Boedijn, C. clavata Jain, Curvularia sp., Fusarium oxysporum Sch., Penicillium sp., Rhizopus nigricans Ehrenberg, Rhizopus sp., Syncephalastrum sp. and Trichoderma sp. Apergillus niger was found to be associated as the predominant fungus with the rotten fruits. DOI: http://dx.doi.org/10.3329/bjb.v41i1.11090 Bangladesh J. Bot. 41(1): 115-117, 2012 (June)